Design and development of LADM-based infrastructure for Turkey - Alkan, M.; Polat, Z. A. (TAYLOR & FRANCIS LTD, 2017)
This paper investigates the adoption of ISO 19152, Geographic information-Land Administration Domain Model (LADM), for improvement of the current Turkey Land Information System (TLIS) data model and provides a brief overview of the current land information system in Turkey emphasising the main issues in creating the national information infrastructure. Then, the general concept of the country profile for Turkey with the adaptation of the LADM is described. In this context, the core data model of TLIS has been reviewed against the corresponding LADM basic classes. The proposed LADM for TLIS can be used to describe LA information in Turkey, although there are similarities, semantic differences and mismatches of classes and attributes between them. The results of study indicate that effective functioning of the information infrastructure requires proper integration of data, proceeded by analysing the contents of existing data sets, indicating key registers and defining a linkage system between them.
Keywords: Land Administration Domain Model (LADM); Turkey Land Information System (TLIS); ISO 19152; LADM for TLIS; ADMINISTRATION DOMAIN MODEL; INFORMATION-SYSTEM; LAND; Engineering; Geology; Remote Sensing